2021
DOI: 10.3389/fbioe.2020.596746
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Cellular Function: The Contribution of the Nucleus in Mechanotransduction

Abstract: Cells sense a variety of different mechanochemical stimuli and promptly react to such signals by reshaping their morphology and adapting their structural organization and tensional state. Cell reactions to mechanical stimuli arising from the local microenvironment, mechanotransduction, play a crucial role in many cellular functions in both physiological and pathological conditions. To decipher this complex process, several studies have been undertaken to develop engineered materials and devices as tools to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 174 publications
(200 reference statements)
0
17
0
Order By: Relevance
“…217 The nuclear LINC complex is located below the nuclear envelope and contains lamin, nesprins, and Sad1 and UNC-84 (SUN) proteins. 218,219 Mechanical deformation of the nucleus induces changes in chromatin organization by a mechanism depending on intracellular calcium release and leading to softening of the nuclear envelope, which is crucial in preventing stretch-induced DNA damage. 220,221 There is also a linear scaling relation between collagen content in the ECM and lamin A contents in the nuclear envelope across different stages of fibrosis, indicating that ECM conditions reflect nuclear mechanics and signaling.…”
Section: Cytoskeleton and Nucleus In Mechanosensation And Mechanotransductionmentioning
confidence: 99%
“…217 The nuclear LINC complex is located below the nuclear envelope and contains lamin, nesprins, and Sad1 and UNC-84 (SUN) proteins. 218,219 Mechanical deformation of the nucleus induces changes in chromatin organization by a mechanism depending on intracellular calcium release and leading to softening of the nuclear envelope, which is crucial in preventing stretch-induced DNA damage. 220,221 There is also a linear scaling relation between collagen content in the ECM and lamin A contents in the nuclear envelope across different stages of fibrosis, indicating that ECM conditions reflect nuclear mechanics and signaling.…”
Section: Cytoskeleton and Nucleus In Mechanosensation And Mechanotransductionmentioning
confidence: 99%
“…However, it is important to consider that the augmentation of cytoskeletal stiffness could be not the direct consequence of the nuclear expansion, but the cause of this phenomenon. In fact, contractile actin structures, thanks to the LINC complex (Linker of Nucleoskeleton and CSK), can directly transmit mechanical forces to the nucleus and the genome at its interior, change its shape and regulate gene expression [ 75 ]. In particular, it has been demonstrated that a strict correlation exists between CSK organization, cell spreading and nuclear shape [ 76 ], indicating that the increased content of F-actin and the cell stiffening could be responsible for changes in nuclear shape.…”
Section: Radiation Effects On the Actin Cskmentioning
confidence: 99%
“…Almost three decades ago, INGBER [73][74][75] coined the term "tensegrity" (tension integration) to describe the information-conducting mechanism through which deformation of cells causes disruption of the self-supporting cortical actin cytoskeleton that is relayed throughout the cell and contributes to mechanosignalling. The actin cytoskeleton also physically interacts with the nuclear lamina, and in this way directly changes the chromatin structure and thus gene expression [76,77]. The tensegrity of cyclically stretched substrates (lungs) has been mathematically modelled [78].…”
Section: Ecm Biomechanics Impact Of Ecm Biomechanics In Terms Of Cell...mentioning
confidence: 99%